Extreme heat impacts on acute care: Examining emergency department visits and hospital admissions during the 2021 British Columbia heatwave - Dylan G. Clark; Elise H. Jackson; Corinne M. Hohl; Kevin E. Liang (Elsevier, 2024)
Introduction: Emergency department (E.D.) visits and hospitalization patterns shifted dramatically during the 2021 extreme heat event (EHE) across the Greater Vancouver Area of southern British Columbia, Canada. Methods: In this ecological timeseries study we analyze E.D. visits (n=36,432) and hospitalizations (n=18,624) between June 4th, 2021, and July 29th, 2021, using data from two administrative databases: (1) the Canadian National Ambulatory Care Reporting System; and (2) and the Canadian Discharge Abstract Database data. Using Mann-U Whitney tests, we compared how E.D. visits, hospitalizations, and patient diagnoses changed during a seven-day EHE and two subsequent lag periods compared to the surrounding baseline period. We also use a distributed lag non-linear model to analyze the relationship between daily maximum temperatures and daily E.D. visits during the study period. Results: We observed a statistically significant increase in overall E.D. visits during the EHE and during the week following the EHE, and a positive relationship between daily maximum temperature and relative risk of an E.D. visit. Further, there were significant increases in critically ill patients presenting to the E.D. during the EHE, based on Canadian Triage Acuity Scale (CTAS) and increases in key diagnoses, including acute kidney failure, heatstroke, and dehydration. Conclusions: Heatwaves have significant impacts on public health and acute care systems beyond heat-related deaths. Complications associated with heat exposure and surges in patient volume have implications for internal medicine, emergency medicine, and psychiatry departments. Better understanding the disease patterns associated with extreme heat events is essential to health system planning and response.